2020
DOI: 10.1101/2020.06.26.174052
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LINE-1 expression in cancer correlates with DNA damage response, copy number variation, and cell cycle progression

Abstract: Retrotransposons are genomic DNA sequences that are capable of copying themselves to new genomic locations via RNA intermediates; LINE-1 is the only retrotransposon that remains autonomous and active in the human genome. The mobility of LINE-1 is largely repressed in somatic tissues, but LINE-1 is active in many cancers. Recent studies using LINE-1 constructs indicate that host cells activate a DNA damage response (DDR) to repair retrotransposition intermediates and resolve conflicts between LINE-1 and DNA rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…However, we also saw a high level of inferred "LINE-1" expression across all cell types (figure 1B). This is an unreasonable result given that previous IHC experiments show that LINE-1 is specifically overexpressed in cancer cells 2 , and our own analyses of tumor transcriptomes and proteomes indicate that LINE-1 expression is highly enriched in tumors compared to adjacent normal tissue 13 . Thus, we concluded that, in this analysis, any signal from LINE-1 has been almost completely overwhelmed by the presence of other transcripts that terminate at or near the 3' end of LINE-1.…”
Section: ' Targeted Scrna-seq Is Not Appropriate For Line-1 Quantitamentioning
confidence: 82%
See 1 more Smart Citation
“…However, we also saw a high level of inferred "LINE-1" expression across all cell types (figure 1B). This is an unreasonable result given that previous IHC experiments show that LINE-1 is specifically overexpressed in cancer cells 2 , and our own analyses of tumor transcriptomes and proteomes indicate that LINE-1 expression is highly enriched in tumors compared to adjacent normal tissue 13 . Thus, we concluded that, in this analysis, any signal from LINE-1 has been almost completely overwhelmed by the presence of other transcripts that terminate at or near the 3' end of LINE-1.…”
Section: ' Targeted Scrna-seq Is Not Appropriate For Line-1 Quantitamentioning
confidence: 82%
“…While very strong evidence from both RNA and protein 36,46,47 shows that LINE-1 is highly expressed in many tumors, the extent of its expression in normal cellular contexts is much less well understood. New evidence has linked retrotransposons broadly or LINE-1 specifically to a variety of non-cancer diseases, including age-related inflammation 16,32 , neurodegenerative diseases 4850 and autoimmune disorders 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…However, mechanisms that limit LINE-1 expression are often dysfunctional in cancers, allowing for the expression and mobilization of LINE-1 [28,33,34]. LINE-1 expression has the potential to disrupt genomic stability, making it a likely component in cancer progression [35,36]. LINE-1 ORF1p expression has been observed in around 47% of tumors tested, and roughly in 40% of prostate tumors [33].…”
Section: Introductionmentioning
confidence: 99%